Approximate weak amenability of abstract Segal algebras - Samea, H. (Mathematica Scandinavica, 2010)
In this paper the approximate weak amenability of abstract Segal algebras is investigated. Applications to compact groups are given. Also an open problem raised by Ghahramani and Lau is answered negatively.